1991
DOI: 10.1136/ard.50.11.805
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid syndrome: five year follow up.

Abstract: Nineteen patients out of 250 subjects with antiphospholipid antibodies, who had initially presented to the lupus clinic at St Thomas's Hospital, London five or more years ago with a history of venous/arterial occlusions, were entered into the study. The patients were divided into two main groups: I those who remained well without any further thromboembolic complications (n= 10); H those who developed recurrent thrombotic events in the five year period (n=9).The patients were followed up to determine the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
4

Year Published

1994
1994
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(34 citation statements)
references
References 22 publications
0
30
0
4
Order By: Relevance
“…It has also been confirmed that the use of immunosuppressive drugs and/or corticosteroids has no role in the treatment of Hughes syndrome [30]. The present consensus on the management of recurrent fetal wastage is to give lowdose aspirin (75-150 mg/day) before pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been confirmed that the use of immunosuppressive drugs and/or corticosteroids has no role in the treatment of Hughes syndrome [30]. The present consensus on the management of recurrent fetal wastage is to give lowdose aspirin (75-150 mg/day) before pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…As previous high titres of aCL/aPL may decrease coin cidentally with the thrombotic occlusive event, in that these antibodies might be consumed at the site or at the time of thrombosis [17,39], only other prospective serial evaluations will provide further elements to clarify this point which is crucial mainly with respect to the under standing of the causal relationships between antiphos pholipids and thrombosis. The results are still conflicting, but this fact might also depend on the too little number of clinical studies report ing these data, thus underscoring the need for more exten sive investigations.…”
Section: (5) Look At the Time O F Appearance O F La/acl/apl With Respmentioning
confidence: 99%
“…On the contrary, persistent LA/aCL/ aPL-positive results, beyond the phases of activity of dis ease, do need attention [15,39],…”
Section: Some Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Тогда же были определены основные признаки синд рома, включающие рецидивирующие венозные и/или артери альные тромбозы, спонтанные аборты, тромбоцитопению и се рологические маркеры -антифосфолипидные антитела (аФЛ): волчаночный антикоагулянт (ВА) и антикардиолипиновые ан титела (аКЛ) [2]. Позднее стало ясно, что антифосфолипидный синдром (АФС) может быть самостоятельной нозологической единицей, называемой в этом случае "первичным АФС", или наблюдаться у пациентов с каким-либо аутоиммунным заболе ванием, чаще с системной красной волчанкой (СКВ), и расце ниваться соответственно как "вторичный" АФС [3].…”
unclassified